Peningkatan Hasil Belajar Fisika Siswa Menggunakan Model Pembelajaran Kooperatif Tipe Stad Dengan Media Powerpoint - Sri Handayani Parinduri; Melati Sukma Sitompul (Gravity Journal, 2022)
This research aims to improve students' physics learning outcomes using the STAD-type cooperative learning model with powerpoint media on subject of elasticity and harmonic motion. The research population is all students of class XI IPA of SMA Swasta Kampus which amounts to 2 classes and the sample consists of two classes, namely control classes and experimental classes taken in random sampling clusters. The author applies the STAD-type cooperative learning model with powerpoint media in experimental classes and direct instruction model in control classes. The research instruments used are tests (multiple choice) and non-tests (observations). The average result of the experimental class postes was 79 and the average result of the control class postes was 72. The results showed that there was an increase in student physics learning outcomes using the STAD-type cooperative learning model with powerpoint media by 16.7% with a gain of 0.693 is a medium category.